2019
DOI: 10.1111/vde.12774
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial‐to‐mesenchymal transition and keratinocyte differentiation in equine experimental body and limb wounds healing by second intention

Abstract: Background -The re-epithelialization process in equine wound healing is incompletely described. For epithelial cells to migrate during embryogenesis they undergo epithelial-to-mesenchymal transition (EMT); this phenotypic transition occurs during wound healing in humans and rodents, but it has not been investigated in horses.Hypothesis/objectives -To investigate keratinocyte differentiation and EMT in equine experimental excisional limb and body wounds healing by second intention. Animals -Six adult research h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…The fact that analgesic effect of PEA is suppressed in PPAR-α deficient mice [26] supports this hypothesis. PPAR-α is expressed also in the skin (thus the contact site with AM/ACM grafts) [48] where it promotes differentiation of human epidermal keratinocytes [66], and is upregulated at the edge of the wound during wound healing [67,68]. PEA-mediated activation of PPAR-α also results in the repression of pro-inflammatory NF-Kb [69], which again is profitable for wound healing.…”
Section: Plos Onementioning
confidence: 99%
“…The fact that analgesic effect of PEA is suppressed in PPAR-α deficient mice [26] supports this hypothesis. PPAR-α is expressed also in the skin (thus the contact site with AM/ACM grafts) [48] where it promotes differentiation of human epidermal keratinocytes [66], and is upregulated at the edge of the wound during wound healing [67,68]. PEA-mediated activation of PPAR-α also results in the repression of pro-inflammatory NF-Kb [69], which again is profitable for wound healing.…”
Section: Plos Onementioning
confidence: 99%
“…A recent study also showed differences in the reepithelialisation process at the molecular level between J o u r n a l P r e -p r o o f horse body and limb wounds. CK10 and loricrin, two markers of late epithelial differentiation, were found to be expressed in some cells at the migrating epithelial tip of body wounds but not of limb wounds, suggesting a more rapid and superior differentiation of keratinocytes in body wounds (Jørgensen et al, 2019b).…”
Section: The Proliferation Phasementioning
confidence: 94%
“…The growth of EGT physically hinders keratinocyte migration as these cells are unable to cover the rapidly proliferating irregular granulation tissue (Hackett, 2011;. Moreover, the mitotic activity of the epithelial cells was markedly lower when the EGT protruded maximally, which may suggest that EGT inhibits the mitosis necessary for reepithelialisation (Wilmink et al, 1999b;Jørgensen et al, 2019b). A recent study also showed differences in the reepithelialisation process at the molecular level between J o u r n a l P r e -p r o o f horse body and limb wounds.…”
Section: The Proliferation Phasementioning
confidence: 99%
“…Similarly, keratocytes explanted from the wounds of zebrafish exhibit loss of E-Cadherin expression and an increase in NCAD (McDonald et al, 2013). These results were recapitulated in the wounds of horses, in which the loss of E-Cadherin and increase in NCAD were concentrated in the epithelium directly adjacent to the wound (Jørgensen et al, 2019).…”
Section: N-cadherin (Ncad)mentioning
confidence: 66%